An International Consensus Practical Guide on Left Atrial Appendage Closure for the Non-implanting Physician: Executive Summary - Potpara, Tatjana; Grygier, Marek; Haeusler, Karl Georg; Nielsen-Kudsk, Jens Erik; Berti, Sergio; Genovesi, Simonetta; Marijon, Eloi; Boveda, Serge; Tzikas, Apostolos; Boriani, Giuseppe; Boersma, Lucas V. A.; Tondo, Claudio; Potter, Tom De; Lip, Gregory Y. H.; Schnabel, Renate B.; Bauersachs, Rupert; Senzolo, Marco; Basile, Carlo; Bianchi, Stefano; Osmancik, Pavel; Schmidt, Boris; Landmesser, Ulf; Doehner, Wolfram; Hindricks, Gerhard; Kovac, Jan; Camm, A. John (Thrombosis and Haemostasis, 2024)
Many patients with atrial fibrillation (AF) who are in need of stroke prevention are not treated with oral anticoagulation or discontinue treatment shortly after its initiation. Despite the availability of direct oral anticoagulants (DOACs), such undertreatment has improved somewhat but is still evident. This is due to continued risks of bleeding events or ischemic strokes while on DOAC, poor treatment compliance, or aversion to anticoagulant therapy. Because of significant improvements in procedural safety over the years left atrial appendage closure (LAAC), using a catheter-based, device implantation approach, is increasingly favored for the prevention of thromboembolic events in AF patients who cannot have long-term oral anticoagulation. This article is an executive summary of a practical guide recently published by an international expert consensus group, which introduces the LAAC devices and briefly explains the implantation technique. The indications and device follow-up are more comprehensively described. This practical guide, aligned with published guideline/guidance, is aimed at those non-implanting physicians who may need to refer patients for consideration of LAAC.
Keywords: anticoagulation; atrial fibrillation; bleeding; left atrial appendage closure; left atrial appendage occlusion; stroke; prevention